3‐D Nanofabrication of Silicon and Nanostructure Fine‐Tuning via Helium Ion Implantation (Adv. Mater. Interfaces 10/2022). Issue 10 (4th April 2022) - Wen, Xiaolei; Mao, Renwei; Hu, Huan
Abstract : Fine‐Tuning of Nanostructures via Helium Ion Implantation In article number 2101643, Xiaolei Wen, Renwei Mao, and Huan Hu invent an approach for producing 3D silicon nanostructures with super small roughness based on substrate swelling caused by implantation of focused helium ion beams. Furthermore, mimicking the leaning tower of Pisa, they implant on the bottom of the readily made nanostructures to fine‐tune the distance into sub 5‐nm as well as the tilting angles.